Mexican cartel negotiative interactions with the state - Dulin, Adam (Trends in organized crime)
This research applies pure sociology to the negotiation activity of Mexican drug trafficking organizations (DTOs). By operationalizing status along several social dimensions, the author employs crisp set Qualitative Comparative Analysis (cs QCA) to identify unique status configurations associated with negotiative interactions with the state. The results indicate that high status configurations are unique to groups that utilize negotiations in a particular territory. These findings provide further insight into the different positions of strength from which DTOs will pursue non-violent activity.